Nimfes al Vinalopó. La poesia renaixentista d'un alacantí oblidat, Josep Gosalbes de Cunedo (s. XVI). - BIOSCA I BAS, ANTONI (Scripta, 2013)
The work of the 16th. century poet from Alicante Joseph Gosalbes of Cunedo has been forgotten. Some aspects of his life and work deserve attention, at least because he had written about topics of their own land. Some of his poems deal with the former Region of Orihuela, in the south of Valencia kingdom, and celebrate the creation of the diocese of Orihuela, so the author describes this territory in a Renaissance style. His friendship with the humanist Justus Lipsius mark his biography, where wars and prison are also present.